Phage-hunting: mapping viromes against 8000 bacterial genomes (2017)
Several prophage-finding tools have been developed since the 2000's, but these tools rely mostly on available databases and phage-related predicted proteins. Recently, more and more virome sequencing projects are becoming available, most of them with only partial analyses, thus increasing the available data in public databases. In this study, 60 Gb of purified virome reads, from three different projects (one from oceanic samples and two from human gut) were mapped using Bowtie2 against 8164 bacterial genomes. Genomes were first filtered according to read coverage, then several statistical parameters were computed for the 3000 remaining candidates, in order to determine possible discriminative criteria. By manual curation using IGV, forty final candidates were selected and compared with other phage-prediction tools. Ten additional genomes were evaluated for concordance between bacterial environments and viral-reads sources. Twelve new prophages were detected. Here, a potential new method for phage detection and discovery is proposed, which will expand the current knowledge and reveal a more realistic estimation of both bacteriophages and host diversity